Pengaruh Pembayaran Cashless, Inflasi, dan Indeks Pembangunan Manusia terhadap Tingkat Pengangguran di Indonesia - Fitri Lestari; Nurjannah Rahayu Kistanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Indonesia is one of the developing countries that is still improving its economic development to become a developed country. As a country that is improving its economy, of course Indonesia has macroeconomic problems, one of which is unemployment. Unemployment is defined as a situation where the labour force does not have a job and is actively looking for work. This is due to the limited number of jobs available. This study aims to determine and analyse the effect of non-cash payments, inflation, and HDI on the unemployment rate in Indonesia. This research is a quantitative study using panel data for the period 2019-2023 with 34 provinces in Indonesia as observations. The analysis method used is panel data regression. Based on the model selection results with the Hausman test, the fixed effect model (FEM) is the right model to use in this study. The result shows that the RTGS transaction value variable has a negative and insignificant effect on the unemployment rate with a coefficient of -0.339713. The variable of debit/ATM card transaction value negatively and significantly affects the unemployment rate with a coefficient of -1.829781. The credit card transaction value variable has a negative and significant effect on the unemployment rate with a coefficient of -5.822728. The inflation variable has a negative and insignificant effect on the unemployment rate with a coefficient of -0.038126. The human development index variable has a negative and significant effect on the unemployment rate with a coefficient of -0.228593.